The Comparison of COVID-19 Preventive Strategies in Indonesia, Turkey, and China Based on the Number of New COVID-19 Cases in 2020 - Nur Rachmawati Maulida; Yasmin Karimah Ikhsan; Anastasya Annisa Karlina; Asmahan Farah Adiba; Alfian Nur Rosyid (Indonesian Archives and Biomedical Sciences, 2022)
Background; There is no specific drug for COVID-19 yet, therefore it is important to focus on preventing its spread in the community. COVID-19 prevention strategies in each country are certainly different. This review will compare strategies to prevent COVID-19 in Indonesia, Turkey, and China by the number of COVID-19 new cases. Reviews; The number of new cases in Turkey showed a decline after implementing social distancing policies, calling for activities from home, and implementing policies to limit the mobility of people, especially vulnerable groups. In China, the number of new cases shows a decline and tends to ramp up until there are no new cases for some time with additional preventive measures (different from others) shifting offline consultations and treatment to online. In Indonesia, the prevention strategy to stop the spread of COVID-19 which is almost the same as in other countries, but the number of new positive cases of COVID-19 continues to increase. Conclusion; China and Turkey can be said to have succeeded in preventing the spread of COVID-19 by restricting people's entry and exit policies in an area, working from home, and having a good health system, meanwhile Indonesia's COVID-19 new cases tend to continue to increase because of lack of hygiene awareness. Keywords: COVID-19, Prevention, Indonesia, Turkey, China